Dokumentacja badania sprawozdania finansowego a wymogi w tym zakresie wynikające z norm wykonywania zawodu biegłego rewidenta - Szafraniec, Jadwiga (Audit Report Documentation vs. Requirements Within the Scope of Auditor Profession Standards, 2005)
Audit documents that are the result of a financial statement research, contain a set of audit evidence which allow to reach justified conclusions. These conclusions will be the foundation to giving an opinion about this financial statement. This documentary evidence should be sufficient and of appropriate quality for each statement presented by and auditor in his opinion and financial statement report.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 137-145